Historical and Dialectical Perspectives on the Teaching of Aboriginal and Torres Strait Islander Musics in the Australian Education System - Mackinlay, Elizabeth; Dunbar-Hall, Peter (The Australian Journal of Indigenous Education, 2003)
Abstract Indigenous studies (also referred to as Aboriginal and Torres Strait Islander studies) has a double identity in the Australian education system, consisting of the education of Indigenous students and education of all students about Aboriginal and Torres Strait Islander cultures and histories. Through explanations of the history of the inclusion of Aboriginal and Torres Strait Islander musics in Australian music education, this article critiques ways in which these musics have been positioned in relation to a number of agendas. These include definitions of Aboriginal and Torres Strait Islander musics as types of Australian music, as ethnomusicological objects, as examples of postcolonial discourse, and as empowerment for Indigenous students. The site of discussion is the work of the Australian Society for Music Education, as representative of trends in Australian school-based music education, and the Centre for Aboriginal Studies in Music at the University of Adelaide, as an example of a tertiary music program for Indigenous students.